Intravenous tPA in the treatment of acute stroke related to aortic dissection. Issue 6 (3rd June 2019) - Shivkumar, Vikram; Nemade, Dipali
Abstract : A 61-year-old woman with no prior medical illness presented with acute onset stroke symptoms. She had no chest pain at the time of presentation. However, CT angiogram showed an extensive aortic dissection, resulting in hypoperfusion of the right cerebral hemisphere and thus causing stroke symptoms. Due to this finding, tissue plasminogen activator was not given and a negative outcome was avoided.